A Case Study on Teachers' Strategies for Teaching Reading Comprehension in the Context of Emancipated Curriculum - Nurhusliya; Saputra, Eko (Journal of English Education, 2024)
An efficient classroom learning process is typically necessary to produce good lesson outcomes. The purpose of this study was to look into how teachers use the Merdeka Curriculum to teach reading comprehension. This study used a qualitative method with a case study approach, involving two English teachers who were selected as participants through a purposive sampling technique. Data were collected through triangulated with interview, then analyzed thematically. The results showed that the teachers used the following strategies: (1) Think Aloud, (2) Reciprocal Teaching, and (3) SQ3R. This study contributed to provide an overview of the strategies used by teachers to teach reading comprehension and provide a reflection of how English teachers' teaching strategies reflect the implementation of the Emancipated Curriculum. Therefore, teachers need to understand the needs and characteristics of students and relate their teaching strategies to this Emancipated Curriculum.